Workshop Perubahan Dimensi Prima Pelayanan Publik Masa Pandemi - Supawanhar, Supawanhar; Suard, Sabina; Sawadi, Marhan; Prakosa, Amir; Zahari, Muhammad (Jurnal Kewirausahaan dan Bisnis, 2021)
This workshop aims to analyze how key dimensions of public services have changed significantly during the COVID-19 pandemic. In the context of the pandemic, public services have become increasingly important in response to evolving community needs. Through this workshop, stakeholders will identify significant changes in public service dimensions, including accessibility, speed, and responsiveness. Emphasis on innovation and adaptation will be the main focus of this workshop to address the challenges faced by public service institutions. An in-depth analysis of how technology and digitalization have affected the way public services are delivered will be one of the main topics in the workshop discussions. In addition, the workshop will also explore the important role of community participation in improving the effectiveness of public services amidst the pandemic. The discussion will focus on strategies to increase community involvement in the process of public service change. In addition, it will also discuss the important role of leadership and management in managing the changes needed to improve the quality of public services. The workshop will also discuss the challenges faced by public service agencies in adopting new practices and adapting to the changing environment.